Construction patterns of birds’ nests provide insight into nest-building behaviours - Lucia Biddle; Adrian M. Goodman; D. Charles Deeming (PeerJ, 2017)
Previous studies have suggested that birds and mammals select materials needed for nest building based on their thermal or structural properties, although the amounts or properties of the materials used have been recorded for only a very small number of species. Some of the behaviours underlying the construction of nests can be indirectly determined by careful deconstruction of the structure and measurement of the biomechanical properties of the materials used. Here we examined this idea in an investigation of Bullfinch (Pyrrhula pyrrhula) nests as a model for open-nesting songbird species that construct a “twig” nest, and tested the hypothesis that materials in different parts of nests serve different functions. The quantities of materials present in the nest base, sides and cup were recorded before structural analysis. Structural analysis showed that the base of the outer nests were composed of significantly thicker, stronger and more rigid materials compared to the side walls, which in turn were significantly thicker, stronger and more rigid than materials used in the cup. These results suggest that the placement of particular materials in nests may not be random, but further work is required to determine if the final structure of a nest accurately reflects the construction process.